2001
DOI: 10.4049/jimmunol.166.12.7496
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Phagocytosis of the Amyloid β-Peptide in Microglia Is Differentially Modulated by C1q

Abstract: Microglial ingestion of the amyloid β-peptide (Aβ) has been viewed as a therapeutic target in Alzheimer’s disease, in that approaches that enhance clearance of Aβ relative to its production are predicted to result in decreased senile plaque formation, a proposed contributor to neuropathology. In vitro, scavenger receptors mediate ingestion of fibrillar Aβ (fAβ) by microglia. However, the finding that cerebral amyloid deposition in a transgenic mouse model of Alzheimer’s disease was diminished by inoculation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 48 publications
7
77
1
Order By: Relevance
“…We found that cytochalasin D treatment resulted in an ϳ70% reduction in A␤ ingestion by BV-2 cells overexpressing M-CSFR. This level of A␤ phagocytosis inhibition is similar to that observed with cytochalasin D for primary rodent microglia (26). These results, along with those showing low cell surface binding and confocal images showing Fluo-A␤ internalization, demonstrate that M-CSFRinduced internalization is phagocytic.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…We found that cytochalasin D treatment resulted in an ϳ70% reduction in A␤ ingestion by BV-2 cells overexpressing M-CSFR. This level of A␤ phagocytosis inhibition is similar to that observed with cytochalasin D for primary rodent microglia (26). These results, along with those showing low cell surface binding and confocal images showing Fluo-A␤ internalization, demonstrate that M-CSFRinduced internalization is phagocytic.…”
Section: Discussionsupporting
confidence: 70%
“…Uptake of A␤ not blocked by fucoidan may have been because of interactions between A␤ and other microglial receptors. Although we used serum-free medium or media containing heat-inactivated serum, microglia express C1q and its receptor (31), which could also have been involved in uptake of A␤ (26). These results suggest that increased M-CSFR expression activates multiple pathways involved in the internalization of A␤.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Phagocytosis was assessed following previous methods with some modifications (36,62). First, BV2 cells (63) (3.0 × 10 5 cells per well) were exposed to either proinflammatory cytokine IL-1β (20 ng/mL; Thermo Fisher Scientific) or 0.1% BSA in PBS for 10-12 h. After IL-1β or PBS preexposure, the cells were changed to serum-free DMEM and then exposed to fAβ (10 μg/mL) with murine IgG (0.5 mg/mL; Jackson ImmunoResearch Laboratories) or PBS for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%